2008
DOI: 10.1017/s0022215108004192
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of conventional versus endoscopic septoplasty for limited septal deviation and spur

Abstract: No statistically significant difference was found between the conventional and endoscopic septoplasty groups, as assessed by subjective and objective evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 13 publications
6
36
0
7
Order By: Relevance
“…However, post-operative complications such as hemorrhage, infraorbital edema and nasal pain were slightly more in the conventional septoplasty group. 5 We conducted the current study to compare the usefulness and outcomes of endoscopic septoplasty with conventional septoplasty in terms of relief of symptoms, anatomical correction and complications in patients with DNS who had undergone septoplasty by conventional or endoscopic technique at our tertiary care centre.…”
mentioning
confidence: 99%
“…However, post-operative complications such as hemorrhage, infraorbital edema and nasal pain were slightly more in the conventional septoplasty group. 5 We conducted the current study to compare the usefulness and outcomes of endoscopic septoplasty with conventional septoplasty in terms of relief of symptoms, anatomical correction and complications in patients with DNS who had undergone septoplasty by conventional or endoscopic technique at our tertiary care centre.…”
mentioning
confidence: 99%
“…13 Another study from New Delhi showed that complications of septoplasty like haemorrhage, infraorbital edema and nasal pain were lower in patients who underwent endoscopic septoplasty than patients who had conventional procedures. 14 Studies done in other developing nations also showed similar efficacy for endoscopic septoplasty. A study from Nepal showed that the procedure is effective in reduction of symptoms associated with DNS such as rhinorrhoea, nasal obstruction and headache.…”
Section: Discussionmentioning
confidence: 84%
“…In another study conducted by Bothra et al minor complications like hemorrhage, infraorbital edema and nasal pain were more in patients who underwent conventional septoplasty. 9 Synechae persisted in two patients of each group. In this study, two patients in conventional septoplasty group had intraoperative hemorrhage and only one patient in the endoscopic septoplasty group had this.…”
Section: Discussionmentioning
confidence: 88%